ANALISIS PENGELOLAAN PERSEDIAAN BAHAN BAKU SAYURAN DI KITCHEN JW MARRIOTT HOTEL SURABAYA - Azizah Rachmawati; Any Sutiadiningsih; Ita Fatkhur Romadhoni; Mafisa Restami (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Vegetable raw material inventory management is an important aspect in supporting smooth operations and maintaining product quality in the hospitality industry. This study aims to analyze material requirement planning, procurement or ordering of materials, material receipt, material storage, material inventory, preparation or processing of materials, and evaluation of vegetable raw material inventory in the kitchen of JW Marriott Hotel Surabaya. This study uses a qualitative approach with a phenomenological research type. Research informants consist of Sous Chef, Commis Chef, and Casual Staff. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis is carried out through data reduction, data presentation, and drawing conclusions. Data validity is tested using source triangulation and technical triangulation. The results of the study indicate that material requirement planning is carried out based on menu and production needs, material procurement is carried out through ordering from suppliers as needed, material receipt is carried out by checking the quality and quantity of materials received, material storage applies temperature settings and the FIFO principle according to material characteristics, material inventory is controlled by monitoring stock availability, preparation is carried out according to applicable operational standards, and inventory evaluation is carried out to ensure conformity between material use and operational needs. In general, the management of vegetable raw material inventory has been running well, supporting smooth operations, maintaining product quality, and serving as an evaluation tool to improve inventory management effectiveness and minimize the risk of damage and waste.